Pengaruh Pengawasan, Lingkungan Kerja dan Fasilitas Kerja Terhadap Kepuasan Kerja pada PT Perkebunan Nusantara IV Regional II Medan - Aulita, Marshanda; Nasution, Fitra Arlina; Rahayu, Sri; Robain, Wilchan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The research analysis aims to analyze the influence of supervision, work environment and work facilities on job satisfaction at PT. Perkebunan Nusantara IV Regional II Medan. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. The sample in this study was 40 respondents. Primary data collection uses a questionnaire. This research uses multiple linear regression analysis. The research results show that the test results for the work supervision variable show a tcount value of 6.436 > ttable of 2.02 with a significant value of 0.000 <0.05, so hypothesis H1 is accepted and H0 is rejected, meaning that supervision has a partially positive and significant effect on job satisfaction at PT. Perkebunan Nusantara IV Regional II Medan. The test results for the work environment variable show a tcount value of 6.306> ttable of 2.02 with a significant value of 0.000 <0.05, so the hypothesis H2 is accepted and H0 is rejected, meaning that the work environment has a partially positive and significant effect on job satisfaction at PT. Perkebunan Nusantara IV Regional II Medan. The test results for the work facilities variable show a tcount value of 1.657 < ttable of 2.02 with a significant value of 0.106 > 0.05, so hypothesis H3 is accepted and H0 is rejected, meaning that work facilities have a partially positive and significant effect on job satisfaction at PT Perkebunan Nusantara IV Regional II Medan.